Re-emerging syphilis: a detrended correspondence analysis of the behaviour of HIV positive and negative gay men - Syed Qutub; Clark Pete; Cook Penny A; Wheater C; Bellis Mark A (BMC, 2003)
Abstract Background Recent syphilis outbreaks in the UK have raised serious concerns about the sexual health of the population. Moreover, syphilis appears more likely to facilitate HIV transmission than any other sexually transmitted infection (STI). Methods The sexual and other risk behaviour of a sample of HIV positive and negative gay men with and without syphilis was subjected to a detrended correspondence analysis (DCA). Results A DCA plot was used to illustrate similarity of individuals in terms of their behaviours, regardless of their infection status. The majority of those with syphilis (78%; 18/23) fell into a high-risk group with more partners, and use of anonymous sex venues and drugs during sex. However, 16% of uninfected controls (8/49) and 62% of HIV positive individuals without syphilis (8/13) also fell into this high-risk group. Conclusions Using a statistical technique that is novel for this type of investigation, we demonstrate behavioural overlaps between syphilis-infected individuals in an ongoing UK outbreak and uninfected HIV positive and negative controls. Given the high-risk behaviour of a significant proportion of uninfected individuals, ongoing transmission of syphilis and HIV in this population seems likely.